2022
DOI: 10.1093/nar/gkac688
|View full text |Cite
|
Sign up to set email alerts
|

The influenza A virus genome packaging network — complex, flexible and yet unsolved

Abstract: The genome of influenza A virus (IAV) consists of eight unique viral RNA segments. This genome organization allows genetic reassortment between co-infecting IAV strains, whereby new IAVs with altered genome segment compositions emerge. While it is known that reassortment events can create pandemic IAVs, it remains impossible to anticipate reassortment outcomes with pandemic prospects. Recent research indicates that reassortment is promoted by a viral genome packaging mechanism that delivers the eight genome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…In conclusion, since RNA structure constraints appear to suppress sequence variation, RNA motifs of high structural and sequential conservation, such as 79–93, 2301–2311 (vRNA2, Table 4 ); 1527–1550 (vRNA5, Table 5 ); 788–809, and 995–1004 (vRNA7, Table 6 ) have great functional potential. These motifs are all located in regions identified as terminal packaging signals for IAV genome assembly (reviewed in [ 87 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, since RNA structure constraints appear to suppress sequence variation, RNA motifs of high structural and sequential conservation, such as 79–93, 2301–2311 (vRNA2, Table 4 ); 1527–1550 (vRNA5, Table 5 ); 788–809, and 995–1004 (vRNA7, Table 6 ) have great functional potential. These motifs are all located in regions identified as terminal packaging signals for IAV genome assembly (reviewed in [ 87 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In our structural study, we found several small hairpins and motifs within this region but these have rather low base-pairing probability as well as structural conservation. It is worth noting that this may be a result of evolutionary pressure to preserve intersegmental interactions, especially since the 40–260 nt region has been shown in previous research to be a 5ʹ end packaging signal [ 19 , 87 ]. Two regions 40–255 and 1340–1405 nt of vRNA3 were identified as taking part in vRNA-vRNA interactions in A/WSN/1933 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of 8 gene segments enclosed in an enveloped virion which is 100 nm in diameter. 29 , 30 Haemagglutinin (HA), matrix (M), neuraminidase (NA), nucleoprotein (NP), non‐structural protein (NS1), polymerase acidic protein (PA), polymerase basic protein 1 (PB1), and polymerase basic protein 2 (PB2) are the eight IAV gene segments which encode protein(s) with specific functions. 31 , 32 The segmented genome of IAV has important implications in virus evolution and immune escape.…”
Section: Structure Genome Host Ranges and Mode Of Transmissionmentioning
confidence: 99%
“…IAV is a segmented negative‐sense single‐stranded RNA (ssRNA) virus belonging to the Orthomyxoviridae family. It consists of 8 gene segments enclosed in an enveloped virion which is 100 nm in diameter 29,30 . Haemagglutinin (HA), matrix (M), neuraminidase (NA), nucleoprotein (NP), non‐structural protein (NS1), polymerase acidic protein (PA), polymerase basic protein 1 (PB1), and polymerase basic protein 2 (PB2) are the eight IAV gene segments which encode protein(s) with specific functions 31,32 .…”
Section: Structure Genome Host Ranges and Mode Of Transmissionmentioning
confidence: 99%
“…These signals, accountable for direct vRNA–vRNA interactions, display segment and subtype specificity and have been mapped throughout the entire length of the vRNAs ( 9 19 ). Hence, the current model for vRNA packaging, which also relies on structural ( 20 ) and genetic data ( 21 25 ), is that vRNA–vRNA interactions between adjacent packaging signals control the bundling of the eight viral segments and their copackaging into virions with a conserved “7 + 1” pattern, with one central segment surrounded by seven others ( 16 , 26 , 27 ). Direct contacts between segments have been observed by electron tomography ( 10 , 28 ).…”
mentioning
confidence: 99%